2015
DOI: 10.1016/j.immuni.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 Requires the Pannexin-1 Channel and the Purinergic P2X7 Pore to Mediate Pyroptosis and Endotoxic Shock

Abstract: SUMMARY The noncanonical inflammasome induced by intracellular lipopolysaccharide (LPS) leads to caspase-11-dependent pyroptosis which is critical for induction of endotoxic shock in mice. However, the signaling pathway downstream of caspase-11 is unknown. We found that cytosolic LPS stimulation induced caspase-11-dependent cleavage of the pannexin-1 channel and ATP release, which in turn activated the purinergic P2X7 receptor to mediate cytotoxicity. In the absence of P2X7 or pannexin-1, pyroptosis induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
446
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(460 citation statements)
references
References 43 publications
10
446
3
1
Order By: Relevance
“…Furthermore, pyroptosis, which is associated with a highly inflammatory state induced by intracellular pathogens, has been reported to possibly contribute to an inflammatory syndrome in vivo [115]. In the non-canonical inflammasome pathway, it has been demonstrated that upon intracellular lipopolysaccharide (LPS) stimulation, caspase-11 cleaves the pannexin-1 channel resulting in the release of ATP, which in turn activates P2X7 to induce cytotoxicity and pyroptosis [116,117]. Recent findings have suggested that the presence of cytosolic LPS dramatically decreases the threshold concentration of ATP necessary to drive the opening of the P2X7 channel, which allows the release of proinflammatory cytokines such as IL-1b.…”
Section: Regulation Of Inflammasome Activity and Il-1b Secretion Pyromentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pyroptosis, which is associated with a highly inflammatory state induced by intracellular pathogens, has been reported to possibly contribute to an inflammatory syndrome in vivo [115]. In the non-canonical inflammasome pathway, it has been demonstrated that upon intracellular lipopolysaccharide (LPS) stimulation, caspase-11 cleaves the pannexin-1 channel resulting in the release of ATP, which in turn activates P2X7 to induce cytotoxicity and pyroptosis [116,117]. Recent findings have suggested that the presence of cytosolic LPS dramatically decreases the threshold concentration of ATP necessary to drive the opening of the P2X7 channel, which allows the release of proinflammatory cytokines such as IL-1b.…”
Section: Regulation Of Inflammasome Activity and Il-1b Secretion Pyromentioning
confidence: 99%
“…This further leads to P2X7 forming a receptor pore, allowing it to respond to the nanomolar concentration of released ATP. During the course of pyroptosis, ATP mostly works as an autocrine signal that targets the cells primed with hypersensitive P2X7 channels (such as those in which cytosolic LPS were detected) [116]. In addition, pannexin-1 was suggested to be necessary for mediating IL-1b release due to caspase-11 activation triggered by pannexin-1-mediated K ?…”
Section: Regulation Of Inflammasome Activity and Il-1b Secretion Pyromentioning
confidence: 99%
“…Recently, Yang and collaborators presented data indicating that pannexin-1 and P2X7R are required for susceptibility to endotoxic shock in mice induced via the non-canonical inflammasome pathway [74]. However, how P2X7R regulates the caspase-11 activation and what the role of pannexin-1 is in this process is not known yet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although residues participating in oligomerization and membrane insertion were proposed, the structural basis of gasdermin-N pore formation remains to be fully elucidated. In addition to gasdermin, a cytotoxicity mediated by pannexin1-P2X7 was reported recently (Yang et al, 2015). Caspase-11-dependent cleavage of the pannexin-1 allows the release of ATP which further activates P2X7 to mediate pyroptosis.…”
mentioning
confidence: 99%
“…A crucial substrate of inflammatory caspases, gasdermin D (GSDMD), was independently identified by several groups in 2015 (He et al, 2015;Kayagaki et al, 2015;Shi et al, 2015). According to their results, GSDMD is cleaved by the activated caspases-1/4/5/11 between its N-terminal and C-terminal domains.…”
mentioning
confidence: 99%